Abducens Nerve Paralysis Caused due to Increased Intracranial Pressure: A Case Report and Review of Literatures: - Haji Naghi Tehrani, Khadijeh; Morshedian, Zahra (Galen Medical Journal, 2017)
Background: Double vision due to abducens nerve palsy in patients with Pseudotumor cerebri is a very rare finding and usually occurs by increasing in intracranial pressure (ICP) and therefore by the effect of pressure on abducens nerve. Case Report: A 21-year-old woman has referred to our clinic with symptoms of the headaches, double vision along with nausea and vomiting lasting for three months, with no history of the disease, drug consumption, and the only clinical findings was weighing about 20 Kg for a recent year. In examination VI nerve palsy of the left eye, papilledema of both eyes was reported. The computed tomography (CT) and magnetic resonance imaging (MRI) as a diagnostic test for a patient’s brain lesions shown normal report. Also, other hormone testing and complete blood count were normal. For the next step patient underwent for lumbar puncture (LP), the patient’s cerebrospinal fluid (CSF) pressure was measured more than 120 CmH2O. According to the findings of the examination, patient diagnosed with pseudotumor cerebri and underwent for frequent LP, which during that the headaches and double vision symptoms of patient decreased, which indicates that all signs and symptoms of patients caused by pseudotumor cerebri were due to sudden increase in body weight over the past year. Patient prescribed for Acetazolamide and recommended to lose weight with proper diet. For three months of follow-up, symptoms of increased ICP and papilledema have been cleared. Conclusion: The pseudotumor cerebri is manageable by proper diet, and there is no need for bariatric surgery. [GMJ.2017;6(1):66-69]